THEORIZING THE EU CONDITIONALITY POLICY AND ITS APPLICATION IN WEST AFRICAN COUNTRIES. THE CASE OF CAPE VERDE - Pereira, Jairzinho Lopes (European Scientific Journal, ESJ, 2014)
The EU is a major international donor and a de facto normative power. As such, it uses leverages (including aid support) and its transnational networks to promote long-term structural changes in third countries. These leverages often take the form of conditionality policy. The Cape Verde-EU relations have been intensifying in the last decade resulting in the the signing of a Special Partnership between them. Cape Verde keeps counting on the EU’s financial support to face basic challenges such as the struggle against poverty and the consolidation of its young democracy. This paper provides an historical overview of the EUCape Verde relations and discusses the role of conditionality policy in the shaping of these relations in the last decade. It argues that, although one may contend that the EU agenda for Cape Verde does not escape the logic of EU’s typical development agenda for West Africa, the official rhetoric is that the most adequate pattern for the EU-Cape Verde relations is that of political dialogue and policy convergence rather than that of conditionality policy. This is so, the EU explains, because they share common challenges and face common threats. Besides the country has achieved a considerable level of social and political stability and has a remarkable record when comes to the use of European funds. The contribution of Cape Verde in the security dossier in emphasized and pointed as one of the possible reasons for the absence of explicit conditionality practices in the framework of the Special Partnership.